Chameleon of head and neck diseases: Intraoral actinomycosis - Srisha Basappa; Bharathi Ullagaddi; Mahesh Mysore Shivalingu; Late Naresh Lingaraju (Wolters Kluwer Medknow Publications, 2015)
Actinomycosis is a chronic infectious granulomatous disease caused by saprophytic Actinomyces species. The case discussed in this report is of an adult female patient with a large actinomycotic lesion in the region of the mandibular left second premolar, first and second molars. Provisional diagnosis was made as extragingival pyogenic granuloma. Definitive diagnosis was based on histopathological examination. Since actinomycotic infection has opportunistic characteristics, early diagnosis and proper management of the disease is mandatory to prevent further complications.